Introduction to digital signal processing using MATLAB - Schilling, Robert J. (Australia : Cengage Learning, 2012)
Previous ed. : published as digital signal processing using MATLAB 2005.
Includes bibliographical references and index.
Keywords: Numerical analysis; Signal processing; MATLAB